The antioxidant effect of Beackea frutescence microemulsions dietary supplements on skin absorption studies - Mohd Zul Helmi Rozaini; Armiza Ahmad; Azizul Idris; Chen Fei Low; Mohd Effendy Abdul Wahid (Medical Journals Sweden, 2016)
Objective: To study the effect of two different microemulsions containing Beackea frutescence supplements composed of nerolidool, selenium and vitamin E on absorption effect related to skin health and skin aging. Materials and methods: A total of 39 volunteers with normal and healthy skin were divided into three groups (n = 13) and supplemented for a period of 12 weeks. Group 1 received a mixture of lutein (3 mg/day), lycopene (3 mg/day), α-tocopherol (10 mg/day), selenium (75 μg/day) and β-nerolidool (4.8 mg/day) and Group 2 was supplemented with a mixture of β-nerolidool (4.8 mg/day), lycopene (6 mg/day), selenium (75 μg/day) and α-tocopherol (10 mg/day). Group 3 was the placebo control. Wrinkling, smoothness, scaling and roughness of the skin were determined by Surface Evaluation of Living Skin (Visioscan). Results: Upon supplementation, serum levels of selected nerolidool increased in both groups. Skin thickness and density were determined by ultrasound measurements. A significant increase for both parameters was determined in the serum groups. Roughness and scaling were improved by the supplementation with antioxidant micronutrients. In the placebo group, no changes were found for any of the parameters. Conclusion: Beackea frutescence microemulsion supplements have shown significant change in the texture of human skin as well as scaling, wrinkling, smoothness and roughness were improved by the supplementation.